Antioxidant effects of lotus (Nelumbo nucifera) root and leaf extracts and their application on pork patties as inhibitors of lipid oxidation, alone and in combination. Issue 1 (1st January 2019) - Shin, Dong-Jin; Choe, Juhui; Hwang, Ko-Eun; Kim, Cheon-Jei; Jo, Cheorun
ABSTRACT: Different antioxidant mechanisms of lotus root and leaf were exhibited against lipid oxidation. The effect of lotus root (LRE) and leaf (LLE) extracted with 50% ethanol exhibited high antioxidant activities. It also improved quality and/or oxidative stability of pork patties when extracts were applied individually (1%) or in combination (each 0.5%). The pork patties treated with either LLE or that with LRE exhibited significantly lower peroxide and 2-thiobarbituric acid reactive substances (TBARS) value than the control and patties with LRE. However, the lowest TBARS values were observed in patties with LLE alone from day 7 among the treatments. Patties treated with both LRE and LLE had the highest score in off flavor ( P < 0.05). Hence, the combined effect of LRE and LLE was uncertain and the addition of 1% LLE in patties showed superior antioxidant activity during storage days with an adverse effect on quality properties, except for color.